Comercio en la Comunidad Andina y políticas en la década de 1990 - González Vigil, Fernando (1999)
The purpose of this paper is to explain why the member countries of the Andean Community (AC), have taken so long to complete the Andean Free Trade Area and have repeatedly delayed the deadline for achieving the Andean Customs Union. The go decision-making process arrives to two main findings. First that the top priority for the AC member countries has been to improve their individual chances to negotiate favorable agreements with their major trading partners, which are all outside the AC. Second, that both governments and businesses of the AC member countries rely too heavily on primary exports and tend so to underestimate the importance of the higher value-added content of the intra-AC trade.